Carbapenemase producing Enterobacteriaceae: Environmental reservoirs as primary targets for control and prevention strategies - Ifeyinwa Nkeiruka Nwafia; Anthony Chibuogwu Ike; Ibuchukwu Nkeonyenasoya Orabueze; Walter Chukwuma Nwafia (Nigerian Postgraduate Medical Journal, 2022)
Carbapenemase-producing Enterobacteriaceae (CPE) have become one of the greatest public health challenges globally. In the past decade, antimicrobial resistance (AMR) was viewed as a clinical problem in many parts of the world; hence, the role and magnitude of the contribution of the environment were not well appreciated. This review article was done with online published articles extracted from different databases using search terms related to the work. Evidence has shown that there exists the presence of carbapenemase genes in the environment, consequently fuelling the dissemination with alarming consequences. CPE when acquired causes life-threatening infections in humans. The health and economic impact of these infections are numerous, including treatment failure due to limited therapeutic options which hamper the containment of infectious diseases, further contaminating the environment and worsening the public health challenge. It is a well-known fact that the rate of emergence of resistant genes has outpaced the production of new antimicrobial agents, so it is pertinent to institute effective environmental measures to combat the spread of AMR organisms before it will completely gain a foothold and take us back to 'the pre-antibiotic era'. Environmental sources and reservoirs of resistant genes should therefore be amongst the primary targets for the control and prevention of the spread of resistant genes in the environment. This calls for the effective implementation of the 'one health' strategy with stakeholders committed to the design and enforcement of environmental mitigation policies and guidelines.